A cross-sectional study to assess the attitude towards people living with HIV-AIDS and its determinants among undergraduate medical students in Chennai, 2022 - Murali, Sarath; Subramaniam, Sudharshini; Priyanka, G.; Manikgantan, Sargema (International Journal Of Community Medicine And Public Health, 2025)
Background: Attitudes of medical students toward people living with HIV/AIDS (PLWHA) influence future clinical interactions and care delivery. This study assesses the empathy and avoidance scores among medical students and examines factors associated with these attitudes. Methods: A cross-sectional study was conducted among medical students across pre-clinical, para-clinical and clinical phases. Demographic details, personal experiences with PLWHA and responses to a validated AIDS Attitude Scale were collected. Statistical analysis included Mann Whitney U and Kruskal Wallis tests. Results: The mean age of participants was 21.24 years (SD=1.142). A majority (97.1%) exhibited non-therapeutic attitudes, with only 2.9% displaying supportive attitudes. Female students had higher empathy scores (p=0.010) and lower avoidance scores (p<0.001) than male students. Para-clinical students had higher avoidance scores compared to clinical-phase students (p<0.001). No significant differences were observed based on HIV knowledge or clinical exposure. Students who had personal encounters with PLWHA reported lower empathy scores (p=0.028). Conclusions: Attitudinal gaps persist among medical students toward PLWHA. Gender and phase of study influence empathy and avoidance, while knowledge and exposure alone may not. Educational strategies focusing on reflective learning and stigma reduction may help improve therapeutic attitudes in future healthcare providers.